The Relationship between Anxiety Level and Menstrual Cycle on 11th Grade Student of Kharisma Bangsa High School and Its Review According to the View of Islam - Restie Abeputri; Sri Wahyu Herlinawati; Firman Arifandi (Junior Medical Journal, 2022)
Introduction: Today, mental health disorders are starting to increase, one of which is anxiety disorders. With high levels of anxiety can affect a woman's menstrual cycle where the menstrual cycle becomes irregular. Symptoms that arise from anxiety affect a woman's menstrual cycle. This study aims to determine whether there is a relationship between the level of anxiety with the menstrual cycle in class XI students of SMA Kharisma Bangsa and its review in Islam.Methods: This study used an analytic study with a cross sectional research design. The sample was determined using a total sampling technique with a total sample of 44 respondents. Data collection was done by filling out a questionnaire. Data analysis with Chi-Square Test using SPSS version 25.0.Results: In this study, there were 32 respondents who met the inclusion criteria. The results showed that 6 (18.8%) respondents in the category of not being anxious had regular menstrual cycles. Meanwhile, 5 (15.6%) respondents with moderate anxiety levels and 8 (25%) respondents with severe anxiety levels had irregular menstrual cycles. Based on the Chi-Square Test, a p-value of 0.02 (0.05) was obtained, which indicated that there was a relationship between the level of anxiety and the menstrual cycle in class XI students of SMA Kharisma Bangsa.Conclusion: The level of anxiety can affect the irregularity of the menstrual cycle. Therefore, it is advisable to maintain the level of anxiety by staying calm and not rushing in facing problems or challenges